Thermal investigation on whole plants and plant tissues - Lamprecht, I. (The Nature of Biological Systems as Revealed by Thermal Methods, 2005)
In recent years, plant calorimetry has finished its sleeping beauty dormancy that lasted more or less continuously since the beginning of last century and realizes quite a number of scientifically attractive princes around it. They appeared with new armours and weapons and are eager to dedicate their life to her beauty. New sophisticated calorimeter allow investigations that were excluded before, combination with other highly specific instruments renders more information than gathered earlier by calorimetry alone, rigid and flexible light guides illuminate the otherwise dark vessels and open the field to photosynthesis experiments, infrared thermography provides a means to determine temperature distributions without injuring or even only touching the object. Imagination and technical skill are asked for further developments in plant calorimetry that will for sure come. A special issue of Thermochimica Acta in 2004 will be dedicated to the outcomes of the XIII(th) Conference of the International Society for Biological Calorimetry Energetics of Adaptation and Development — From Molecular Mechanisms to Clinical Practice that took place in Würzburg / Germany 2003. Many contributions deal with photocalorimetry and its application to plant systems as well as with conventional heat flow and combustion calorimetry for plant cells. Among other, topics like A new calorespirometric instrument, Calorespirometric ratios and metabolic efficiency, Energy processes in model plant cells, Heat production and respiration of wheat roots, Calorimetric studies of vegetable tissue wounding, Life zones for key plant species can be predicted with calorespirometry and temperature measurements; Photo-Bio-Calorimetry of Chlorella vulgaris growth, Energetic evaluation of forest formations by bomb calorimetry will be approached. This issue is recommended for further information.